Private security governance in the Malaysian public sector - Vigneswary Pranava, Rasahugan (2024)
The outsourcing of private security services for government agencies is one of the government’s effort to meet the security needs of the public sector’s departments. However, increase in the numbers of private security services has also led to various security issues and challenges, especially in terms of provision and governance. This study aims to examine the provision of private security services in government agencies, in an attempt to establish an ideal private security governance model for the public sector. Therefore, a case study involving three organisations was carried out, which includes the Ministry of Home Affairs, the Office of the Chief Government Security Officer and the Malaysian Security Industry Association. The cross-case analysis revealed five major themes for private security governance namely shared co-governance relationship, divergence in resource management, state-centric compliance mechanism, diminished accountability and agenda transformation. A private security governance model in the context of government departments has been developed. Use of this model is recommended for layered public sector security modes. This study also suggests the formulation of a Private Security Governance Policy and the establishment of a Special Governance Agency for public sector security.